Analisis Yuridis tentang Penentuan Upah Minimum di Indonesia : Kepastian dan Keadilan - Kharisma Nur Azizah Arroyan; Shelvi Rusdiana; Nurlaily Nurlaily (JURNAL HUKUM PELITA, 2025)
The wage system has a fundamental role in guaranteeing workers rights, including the right to earn a decent income to support a dignified life. The Job Creation Law is presented as a major reform in the national labor regulatory framework, with the main aim of increasing investment and encouraging economic growth. However, the implementation of this policy also has consequences that can affect workers' welfare, especially regarding the minimum wage determination mechanism which is very dependent on economic conditions and employment dynamics in each region. Setting minimum wages requires an approach that meets certain criteria to ensure fairness. This research was designed to examine the main issue, namely "To what extent does the implementation of the Job Creation Law affect the fulfillment of workers' rights to wages." Using a juridical-normative approach through a literature review, this research found that disparities in minimum wage determination between provinces and between districts/cities, as regulated in the Job Creation Law, have encouraged some entrepreneurs to move investment to regions with higher minimum wage standards. low. This causes income inequality among workers and has the potential to exacerbate social disparities in wages